2018
DOI: 10.3390/cells7050044
|View full text |Cite
|
Sign up to set email alerts
|

OGT (O-GlcNAc Transferase) Selectively Modifies Multiple Residues Unique to Lamin A

Abstract: The LMNA gene encodes lamins A and C with key roles in nuclear structure, signaling, gene regulation, and genome integrity. Mutations in LMNA cause over 12 diseases (‘laminopathies’). Lamins A and C are identical for their first 566 residues. However, they form separate filaments in vivo, with apparently distinct roles. We report that lamin A is β-O-linked N-acetylglucosamine-(O-GlcNAc)-modified in human hepatoma (Huh7) cells and in mouse liver. In vitro assays with purified O-GlcNAc transferase (OGT) enzyme s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 101 publications
(139 reference statements)
0
16
0
Order By: Relevance
“…Even though such long peptides can be detected by certain types of mass spectrometry (e.g., by using ETD), their identification and site determination are often challenging with other commonly available instruments (e.g., CID mass spectrometry). Instead, less specific enzymes (e.g., chymotrypsin and elastase) and chemical cleavage (e.g., using CNBr) should generate peptides of a size amenable to MS analysis, ,, and in silico digestion will provide helpful information to guide the selection of appropriate enzymes.…”
Section: Characterization Of Individual O-glcnac Proteinsmentioning
confidence: 99%
“…Even though such long peptides can be detected by certain types of mass spectrometry (e.g., by using ETD), their identification and site determination are often challenging with other commonly available instruments (e.g., CID mass spectrometry). Instead, less specific enzymes (e.g., chymotrypsin and elastase) and chemical cleavage (e.g., using CNBr) should generate peptides of a size amenable to MS analysis, ,, and in silico digestion will provide helpful information to guide the selection of appropriate enzymes.…”
Section: Characterization Of Individual O-glcnac Proteinsmentioning
confidence: 99%
“… Simon et al (2018) reported that lamin A could be β-O-linked N-acetylglucosamine-(O-GlcNAc)-modified in human hepatoma (Huh7) cells and in the mouse liver. O-linked glycosylation is the enzymatic addition of O-GlcNAc by the enzyme O-GlcNAc transferase (OGT) to protein Ser/Thr residues ( Hart et al, 2011 ).…”
Section: Other Post-translational Modifications: Methylation Ubiquiti...mentioning
confidence: 99%
“…The mechanisms underlying laminopathies have been extensively investigated. It is currently well recognized that lamins are functionally regulated by a myriad of PTMs, existing under certain biological or pathological conditions with specific functions, including farnesylation ( Farnsworth et al, 1989 ), phosphorylation ( Beausoleil et al, 2004 ; Olsen et al, 2006 ), acetylation ( Choudhary et al, 2009 ; Lundby et al, 2012 ; Weinert et al, 2018 ), SUMOylation ( Lumpkin et al, 2017 ), methylation ( Rao et al, 2019 ), ubiquitination ( Wagner et al, 2011 ; Povlsen et al, 2012 ), and O-GlcNAcylation ( Alfaro et al, 2012 ; Wang et al, 2012 ; Simon et al, 2018 ). PTMs of lamins might directly affect their structure, therefore affecting the functions or destructing LAD binding or its organization and gene expression ( Wong and Stewart, 2020 ), although the roles of different types and specific sites of PTMs remain to be further clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, a growing number of studies have shown that the function of lamin not only at the cellular level but also in disease states is controlled by the PTMs of proteins, including phosphorylation (Machowska et al, 2015), SUMOylation (Moriuchi et al, 2016), glycosylation (Snider and Omary, 2014), farnesylation (Farnsworth et al, 1989), methylation (Rao et al, 2019), o-glcNAcylation (Alfaro et al, 2012;Wang et al, 2012;Simon et al, 2018), succinylation (Weinert et al, 2013), and ubiquitination (Wagner et al, 2011;Povlsen et al, 2012). Farnesylation is special among many PTMs in the regulation of prelamin A.…”
Section: Lamina/c Mutation-related Diseasesmentioning
confidence: 99%